2015
DOI: 10.1093/ntr/ntv082
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Consequences of Implementing Graphic Warning Labels on Cigarette Packs for Tobacco-Related Health Disparities

Abstract: Introduction: Population-level communication interventions, such as graphic warning labels (GWLs) on cigarette packs, have the potential to reduce or exacerbate tobacco-related health disparities depending on their effectiveness among disadvantaged sub-populations. This study evaluated the likely impact of nine GWLs proposed by the US Food and Drug Administration on (1) African American and (2) Hispanic smokers, who disproportionately bear the burden of tobaccorelated illness, and (3) low education smokers, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 33 publications
0
50
0
Order By: Relevance
“…Pictorial warnings were equally effective for diverse population subgroups, including lower-education, lower-income, racial-minority, and sexual-minority smokers, supporting prior research suggesting that pictorial warnings would be unlikely to exacerbate smoking disparities. 26,27 The warnings also increased intentions to quit smoking and forgoing cigarettes, both of which are predictors of subsequent quit attempts. 16 Despite the relatively short duration of the trial, 5.7% of smokers exposed to pictorial warnings had quit smoking for at least 1 week by the end of the trial compared with 3.8% of those exposed to text-only warnings, translating to an absolute increase of 1.9%.…”
Section: Discussionmentioning
confidence: 99%
“…Pictorial warnings were equally effective for diverse population subgroups, including lower-education, lower-income, racial-minority, and sexual-minority smokers, supporting prior research suggesting that pictorial warnings would be unlikely to exacerbate smoking disparities. 26,27 The warnings also increased intentions to quit smoking and forgoing cigarettes, both of which are predictors of subsequent quit attempts. 16 Despite the relatively short duration of the trial, 5.7% of smokers exposed to pictorial warnings had quit smoking for at least 1 week by the end of the trial compared with 3.8% of those exposed to text-only warnings, translating to an absolute increase of 1.9%.…”
Section: Discussionmentioning
confidence: 99%
“…Syntheses of the GHW literature (Hammond, 2011; Noar et al, 2016a, 2016b), coupled with recent experimental evidence (Brewer et al, 2016; Gibson et al, 2015; McQueen et al, 2015), show that such exposure can produce important effects on smoking-related cognitive, affective, and behavioral outcomes. Moreover, our study, together with previous research (Hall et al, 2015; Thrasher et al, 2016), suggests that conversations stimulated by GHW exposure could serve to reinforce and amplify these effects.…”
Section: Discussionmentioning
confidence: 99%
“…As summarized by Cappella (2016), when considering the body of work on GHWs, a “picture of the causal effectiveness of warning labels emerges that is difficult to ignore” (p.132). Recent experimental studies have suggested that GHWs may present an important opportunity to address disparities, as they were similarly effective across diverse racial/ethnic and socioeconomic populations (Cantrell et al, 2013; Gibson et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…In contrast to our findings with SGM populations, researchers have found that GHWs were equally effective among racial/ethnic minorities and lower literacy populations. [30, 54] We may observe communication inequalities by gender and sexual orientation and not by race/ethnicity or literacy because there may have been more efforts to conduct formative research and pilot testing of GHWs with racial/ethnic minorities and those from lower socioeconomic position. [30, 31, 55] In comparison, to our knowledge formative research to inform the design of GHWs from the perspectives of SGM populations may be lacking.…”
Section: Discussionmentioning
confidence: 99%
“…[30, 31] A systematic review concluded that there was no evidence that health warnings impacted socioeconomic inequalities in smoking. [20] In one randomized clinical trial, smokers who were randomly assigned to receive four of the nine FDA-proposed GHWs on their cigarette packs over four weeks (versus those who received text-only warnings) were more likely to make a quit attempt lasting at least one day (40% vs. 34%, respectively).…”
Section: Introductionmentioning
confidence: 99%